The Relationship of Non-Food Consumption Expenditures, Early Marriage, Proper Sanitation and Active Posyandu on Stunting in Indonesia 2017-2021 - Windarti Lutfia Sukadi, Tri; Ratih, Arivina (Lafadz Jaya Publisher, 2024)
Stunting describes chronic malnutrition status during growth and development since early life. In the National Medium Term Development Plan (RPJMN) 2020 - 2024, the Indonesian government set a target for the prevalence of stunting in children under five to only 14% in 2024 (Presidential Decree Number 18 of 2020 concerning RPJMN 2020 - 2024). Efforts were made to see the relationship that causes stunting, non-food consumption expenditure, early marriage, proper sanitation and active posyandu. This research is a type of descriptive research with a quantitative approach using logistic regression with data obtained through the Central Statistics Agency (BPS) for 2017-2021. The Wald test results show that the Non-Food Consumption Expenditure variable receives H0, meaning that there is a negative and significant influence between non-food consumption expenditure on stunting. The variables of early marriage, proper sanitation and active posyandu reject H0, which means that in this study there is a positive and significant influence on stunting. The results of the omnibus test (F) show that the calculated f value is greater than the f table (4.951 > 2.43) with a significance level of (0.000 < 0.05), so H0 is rejected, and Ha is accepted. So, it can be concluded that non-food consumption expenditure, early marriage, proper sanitation and active posyandu simultaneously influence the stunting rate.